2020
DOI: 10.3389/fmicb.2020.01057
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Variant Designed From DLP4 Cationic Peptide Against Staphylococcus aureus CVCC 546

Abstract: Insect defensins are promising candidates for the development of potent antimicrobials against antibiotic-resistant Staphylococcus aureus (S. aureus). An insect defensin, DLP4, isolated from the hemolymph of Hermetia illucens larvae, showed low antimicrobial activity against Gram-positive (G +) pathogens and high cytotoxicity, which limited its effective therapeutic application. To obtain more potent and low cytotoxicity molecules, a series of peptides was designed based on the DLP4 template by changing the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…As shown in Figure 2 A, the circular dichroism (CD) spectra showed that NZ2114 and NZL had a positive peak at 196 nm and two negative peaks at approximately 208 and 228 nm, respectively, which demonstrated that the peptides were characterized by α-helix and β-sheet or random coil in various environments [ 26 ]. However, the CD peak of NZL showed a significant increase in α-helix in 40 mM sodium dodecyl sulfate (SDS) mimicking the bacterial membrane, indicating that NZL tended to form α-helix structure and enhance membrane interactions [ 27 ]. Additionally, the three-dimensional structure modeling result predicted that similar to NZ2114, NZL possessed a typical cystine-stabilized alpha-beta structure (CSαβ) conformation, including an α-helix (residues 12–20), an antiparallel β-sheet (residues 17–31 and 36–40), and three disulfide bonds (Cys4–Cys30, Cys15–Cys37, and Cys19–Cys39) ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 2 A, the circular dichroism (CD) spectra showed that NZ2114 and NZL had a positive peak at 196 nm and two negative peaks at approximately 208 and 228 nm, respectively, which demonstrated that the peptides were characterized by α-helix and β-sheet or random coil in various environments [ 26 ]. However, the CD peak of NZL showed a significant increase in α-helix in 40 mM sodium dodecyl sulfate (SDS) mimicking the bacterial membrane, indicating that NZL tended to form α-helix structure and enhance membrane interactions [ 27 ]. Additionally, the three-dimensional structure modeling result predicted that similar to NZ2114, NZL possessed a typical cystine-stabilized alpha-beta structure (CSαβ) conformation, including an α-helix (residues 12–20), an antiparallel β-sheet (residues 17–31 and 36–40), and three disulfide bonds (Cys4–Cys30, Cys15–Cys37, and Cys19–Cys39) ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of resistant S. hyicus and high morbidity rates (up to 90%) during exudative epidermitis outbreaks often make it a laborious and economically impractical task [ 6 , 7 , 29 , 30 ]. AMPs, as new therapeutic agents in the future, are currently under evaluation, whereas some challenges such as low antimicrobial activity and relatively high cytotoxicity limit their clinical applications [ 27 , 31 ]. It has been argued that the most difficult problem in the development of AMPs is that new candidates without optimization have been put into preclinical and clinical trials too quickly, thereby leading to failure, which highlights the importance of optimization in the early stages of laboratory development [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting study by Li, et al [ 134 ] showed that insect defensins are promising candidates against antibiotic-resistant Staphylococcus aureus . A variant designed from insect defensin DLP 4 , ID 13 exhibited strong antibacterial activity at low MIC values of 4–8 μg/mL to Gram-positive pathogens ( S. aureus, S. epidermidis, S. pneumoniae , S. suis ), which were lower than those of DLP 4 , and cytotoxicity of ID 13 (71.4% viability) was less than that of DLP 4 (63.8% viability).…”
Section: Alternative Methods For Animal Husbandrymentioning
confidence: 99%
“…A variant designed from insect defensin DLP 4 , ID 13 exhibited strong antibacterial activity at low MIC values of 4–8 μg/mL to Gram-positive pathogens ( S. aureus, S. epidermidis, S. pneumoniae , S. suis ), which were lower than those of DLP 4 , and cytotoxicity of ID 13 (71.4% viability) was less than that of DLP 4 (63.8% viability). The authors concluded that ID 13 could be a promising peptide antibiotic agent for therapeutic applications in farms [ 134 ].…”
Section: Alternative Methods For Animal Husbandrymentioning
confidence: 99%